Description and Evaluation of the AACN Synergy Model for Patient Care Employing the Critique Frameworks of Chinn and Kramer (2011) and Fawcett and DeSanto-Madeya (2013). (October 2021) - Hong, Soyun; Kim, Eunkyung
Abstract : This study describes and evaluates the AACN Synergy Model for Patient Care that aligns nurses' competencies with the needs of patients and their families, developed by the American Association of Critical-Care Nurses. The description focuses on objectively explaining the theory, while the evaluation is based on established standards to determine its viability for application in nursing practice. This study applies Chinn and Kramer's (2011) theoretical description method and Fawcett and DeSanto-Madeya's (2013) theory analysis method to evaluate the AACN Synergy Model for Patient Care. Focusing on the patient-nurse relationship, the theory is appropriate for various nursing applications. Abstract : Supplemental Digital Content is Available in the Text.